Transcriptional, Epigenetic and Pharmacological Control of JAK/STAT Pathway in NK Cells - Scarno, Gianluca; Pietropaolo, Giuseppe; Di Censo, Chiara; Gadina, Massimo; Santoni, Angela; Sciumè, Giuseppe (Frontiers in Immunology, 2019)
Differentiation of Natural Killer (NK) cells is a stepwise process having its origin in the bone marrow and proceeding in the periphery, where these cells follow organ specific trajectories. Several soluble factors and cytokines regulate the distinct stages of NK cell differentiation and, ultimately, their functional properties. Cytokines activating the Janus kinases (JAKs) and members of the signal transducer and activator of transcription (STAT) pathway control distinct aspects of NK cell biology, ranging from development, terminal differentiation, activation and generation of cells with adaptive properties. Here, we discuss how the recent advances of next generation sequencing (NGS) technology have led to unravel novel molecular aspects of gene regulation, with the aim to provide genomic views of how STATs regulate transcriptional and epigenetic features of NK cells during the different functional stages.